Structuring and analyzing initiatives that facilitate organizational transformation processes: A sociotechnical approach - Macedo, M.; Ferreira, F.; Dabić, M.; Ferreira, N. (Technological Forecasting and Social Change, 2024)
Change has always been a part of any healthy organization, but the challenges of globalization and current social and technological developments require much more frequent structural transformations. Changes also require key structures and the ability to adapt, which can ensure the success of necessary transformations. The present study presents a decision-support framework that identifies and prioritizes not only the pillars of successful organizational change but also the most essential actions to be taken, thereby contributing to a more holistic outlook on this topic. The analysis applied both a constructivist and creation logic to generate new knowledge based on debate and a learning process involving a panel of relevant experts based on a combination of cognitive mapping and interpretive structural modeling. This approach facilitated the structuring of the problem in question and the identification and prioritization of key variables to be incorporated into the proposed analysis system, which includes cause-effect relationships. No single transformation dimension was shown to be especially prominent, but the results show that most factors fostering the success of transformation processes are related to the actors on whom changes are typically imposed. Transformations thus require organizations to take into account and offset the effects of their employees’ resistance to change. The model developed is a tool that supports organizational transformation planning by offering a realistic, practical understanding of the processes involved.